2020
DOI: 10.1038/s41419-020-2432-1
|View full text |Cite
|
Sign up to set email alerts
|

RAGE acts as an oncogenic role and promotes the metastasis of human lung cancer

Abstract: RAGE (receptor for advanced glycation end-product) is thought to be associated with metastasis and poor prognosis of various types of cancer. However, RAGE is constitutively expressed in the normal lung and down-regulated in cancerous lung, while the opposite evidence shows that RAGE-mediated signaling contributes to the tumorigenesis of lung cancer. Therefore, the role of RAGE in lung cancer progression is still unclear to be further investigated. In this study, RAGE-overexpressed stable clones of human lung … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 49 publications
1
35
0
Order By: Relevance
“…RAGE (receptor for advanced glycation end‐product) is a member of the immunoglobulin superfamily and has been reported to be highly expressed on the surface of macrophages 159 . It has been reported that RAGE overexpression could induce the accumulation of TAMs and thus accelerate the growth of lung cancer xenografts in vivo 160 . Mechanistically, RAGE expression strictly correlates to the metabolic switch in cancer and immune cells.…”
Section: Pharmaceutical Targets Of Tamsmentioning
confidence: 99%
See 2 more Smart Citations
“…RAGE (receptor for advanced glycation end‐product) is a member of the immunoglobulin superfamily and has been reported to be highly expressed on the surface of macrophages 159 . It has been reported that RAGE overexpression could induce the accumulation of TAMs and thus accelerate the growth of lung cancer xenografts in vivo 160 . Mechanistically, RAGE expression strictly correlates to the metabolic switch in cancer and immune cells.…”
Section: Pharmaceutical Targets Of Tamsmentioning
confidence: 99%
“…On one hand, the formation of AGEs could impair the phagocytosis function of M1‐like macrophages within the TME 162 . On the other hand, AGEs could induce RAGE expression in macrophages and their interaction could further promote cancer progression and metastasis by recruiting TAMs 160,163 . Therefore, AGEs/RAGE signaling may also represent a metabolism‐related target for the pharmacological modulation of TAMs, which still needs further investigations.…”
Section: Pharmaceutical Targets Of Tamsmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunohistochemistry. Immunohistochemical assay was performed on the 5 mm thick slides, using mouse anti-human TMSB10 (1:500, Sant cruz, sc-514309) and CD68 (1:1000, CST, 76437) primary antibody, as previously (23). Two experienced investigators independently scored the TAMs-associated TMSB10 without knowing the clinical data.…”
Section: Methodsmentioning
confidence: 99%
“…Immunohistochemistry. Immunohistochemical assay was performed on the 5 mm thick slides, using mouse anti-human TMSB10 (1:500, Sant cruz, sc-514309) and CD68 (1:1000, CST, 76437) primary antibody, as previously (22). Two experienced investigator independently scored the TAMs-associated TMSB10 without knew the clinical data.…”
Section: Methodsmentioning
confidence: 99%